Effect of vitamin D treatment on glucose homeostasis and metabolism in lebanese older adults - El Hajj, Cynthia (2018)
El Hajj, C., Chardigny, J. M., Boirie, Y., Yammine, K., Helou, M., & Walrand, S. (2018). Effect of vitamin D treatment on glucose homeostasis and metabolism in lebanese older adults: A randomized controlled trial. The journal of nutrition, health & aging, 22(9), 1128-1132.